Sustainable approach for CO2 hydrogenation to formic acid with Ru single atom catalysts on nitrogen-doped carbon prepared from green algae - Lee, Kyung Rok; Masudi, Ahmad; Park, Kwangho; Ahn, Sunghee; Lee, Jeong Seop; Sim, Sang Jun; Jung, Kwang-Deog (Elsevier BV, 2024)
Ruthenium catalysts supported on nitrogen-doped carbon (NDC) have gained attention due to their exceptional catalytic performance for CO2 2 hydrogenation to formic acid, a key solution to mitigate CO2 2 emissions. However, conventional methods for preparing NDC typically rely on petrochemical compounds, which are not environmentally friendly. Herein, we propose a sustainable and innovative approach by employing protein-rich green algae as a source to prepare NDC for Ru catalysts. To maximize the CO2 2 reduction effect, flue gas exhausted from industrial processes was utilized as a CO2 2 feed to cultivate the green algae in a photobioreactor. The harvested green algae were pyrolyzed at 800 degrees C under an N2 2 atmosphere to prepare the NDC. After the metalation of Ru on prepared NDC, the Ru catalysts exhibited a turnover number of 7,599 for CO2 2 hydrogenation which demonstrated the potential of green algae as a raw material for NDC. However, the catalysts were deactivated due to the leaching or agglomeration of weakly bound Ru analyzed by experimental and theoretical investigations. We applied a NaBH4 4 treatment to stabilize the Ru active sites, and the treated catalysts retained 99.6 % of their initial catalytic activity after five recycling tests. Furthermore, Ru on NDC achieved a cumulative turnover number of 16,000 after 24 h. This study offers a sustainable and eco-friendly method for reducing CO2 2 emissions, combining the cultivation of green algae with waste flue gas and the production of formic acid via CO2 2 hydrogenation using improved Ru catalysts on algae-derived NDC.